Another way to make information and documentation in digital media - Marcos Recio, Juan Carlos (Revista General de Información y Documentación, 2014)
Digital information is in a constant process of transformation. The data are becoming larger, but not more accurate. The problem to solve is the loyalty of readers and for this research is shown as a needed resource that journalists and documentalists have to employ. In addition, social networks are introduced in the field of information with new formats, with millions of competing with traditional digital media readers. The challenge is to provide the documentalist content, credible and truthful in their midst.
Keywords: Digital information; documentation; social networks; digital newspapers; research